PENINGKATAN KEMAMPUAN KOMUNIKASI DAN PENALARAN MATEMATIS SISWA MADRASAH ALIYAH MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT - Qadriah, Laila; Maryanti, Maryanti (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
Communication skills and mathematical reasoning are one of the goals of mathematics learning. Where communication is defined as the ability to write, read, listen, study, interpret, and evaluate ideas, symbols, terms, and mathematical information. Meanwhile, mathematical reasoning is a brain habit that if developed properly and consistently will make it easier to communicate mathematics both in writing and orally. Therefore, a relevant learning model is needed to optimize, improve, and develop students' communication and mathematical reasoning skills. One of these learning models is  the Teams Games Tournament (TGT) type cooperative learning model. The purpose of this study is to find out: (1) Whether the improvement of communication and mathematical reasoning skills of students who obtain learning with the TGT type cooperative learning model is better than that of students who obtain learning with conventional approaches, and (2) What are the attitudes of students towards mathematics learning who acquire learning with the TGT type cooperative learning model. This study is an experimental research with  a pretest-posttest control research design of the design group. The population in this study is all students of class XI MAN Darussalam Aceh Besar consisting of five classes. Meanwhile, the sample consisted of two classes, namely the experimental class and the control class which were taken by random sampling. The instruments used to obtain research data are in the form of communication and mathematical reasoning ability tests, and attitude scale questionnaires. The statistical test used to analyze data on improving communication skills and mathematical reasoning is a two-track anava test, while the attitude scale questionnaire is calculated based on percentages. The results of the study show that the overall improvement of communication and mathematical reasoning skills of students who obtain learning with the Teams Games Tournament type cooperative learning model  is better than students who acquire learning with conventional approaches. From the results of the student questionnaire, it was concluded that in general, students have a positive attitude towards mathematics learning using the TGT type cooperative learning model